EXPLORING FACTORS CONTRIBUTING TO L2 WILLINGNESS TO READ AMONG INDONESIAN THEOLOGY STUDENTS - Elsha Septia Anaria Wate; Adaninggar Septi Subekti (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
The present study explores possible factors influencing Indonesian theology students’ second/foreign language (L2) Willingness to Read (WTR). This study was the continuation of a survey study involving 41 participants. The present study employed semi-structured interviews. These interviews involved four of the survey participants in the preceding study. Through Thematic Analysis, this study found three factors that improved their L2 WTR. These factors included reading goals, teachers, supporting practices, and alignment of L2 texts with reading preference. Pedagogical implications include allowing flexibility in choosing L2 texts, integrative and interactive reading activities catering to students' diverse preferences, and providing a safe L2 reading environment focusing on constructive feedback from teachers and peers. Directions for future relevant studies include conducting empirical studies on L2 WTR in Indonesia with a broader and deeper scope, considering the scarcity of available studies on L2 WTR in the context.